2015
DOI: 10.1007/s00381-015-2948-3
|View full text |Cite
|
Sign up to set email alerts
|

One-stage posterior focus debridement, fusion, and instrumentation in the surgical treatment of lumbar spinal tuberculosis with kyphosis in children

Abstract: The outcomes of follow-up showed that one-stage posterior focus debridement, fusion, and instrumentation can be an effective treatment method for the lumbar spinal tuberculosis with kyphosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The kyphotic angle, a major indicator of deformity correction and spinal stability reconstruction, was improved significantly after surgery (−4.61° ± 7.31° vs 24.00° ± 13.15°, Z = −4.34, P < .01); the mean deformity correction was 28.61° ± 8.43°, and the mean correction loss at the last follow-up was 1.50° ± 0.90°. Wang et al [17] and He et al [18] reported that the correction angle of lumbar TB in children treated by short-segment fixation and long-segment fixation was 24.2° and 25.2°, the correction loss was 1.2° and 1.1°, respectively; these values were similar to the results of intervertebral surgery in the present study. At the last follow-up, there was no imbalance between anterior and posterior vertebral columns in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The kyphotic angle, a major indicator of deformity correction and spinal stability reconstruction, was improved significantly after surgery (−4.61° ± 7.31° vs 24.00° ± 13.15°, Z = −4.34, P < .01); the mean deformity correction was 28.61° ± 8.43°, and the mean correction loss at the last follow-up was 1.50° ± 0.90°. Wang et al [17] and He et al [18] reported that the correction angle of lumbar TB in children treated by short-segment fixation and long-segment fixation was 24.2° and 25.2°, the correction loss was 1.2° and 1.1°, respectively; these values were similar to the results of intervertebral surgery in the present study. At the last follow-up, there was no imbalance between anterior and posterior vertebral columns in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…However, this surgical strategy greatly increases the operative time, blood loss volume, surgical trauma, and incidence of perioperative complications [57]. In recent years, it has been reported that in cases of progressive single-segment spinal tuberculosis, surgery by a posterior approach can achieve complete debridement, decompression, bone fusion, and internal fixation and can effectively correct spinal kyphosis, which has the advantages of mild trauma, few perioperative complications, low cost, and short recovery time[8, 9]. To analyse the clinical efficacy of different surgical methods for the treatment of thoracolumbar tuberculosis, we retrospectively analysed 132 patients with thoracolumbar tuberculosis treated in 6 hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal TB in children, whose brous rings and endplate cartilage are rich both in blood and lymphatic vessels, are more likely to propagate to different spinal segments than that in adult-aged patients [9]. Furthermore, spinal cords are nourished through smaller epidural spaces and blood vessels in pediatric-aged patients than in comparison to adults, resulting spinal TB a ictions in children with consequential higher related risks of neurological damage [10]. In addition, unbalance in the dynamics of spinal growth between anterior-middle columns, the most frequently involved site of spinal TB, and posterior columns, or heterogeneous types of injuries related to epiphysis of diseased vertebral bodies, makes pediatric-aged patients more prone to scoliosis or kyphosis compared to adult-aged patients.…”
Section: Discussionmentioning
confidence: 99%